Cynaroside: a potential therapeutic agent targeting arachidonate 15-lipoxygenase to mitigate cerebral ischemia/reperfusion injury - Cao, Wenpeng; Hu, Yufeng; Yu, Xingyu; Long, Tingting; Sun, Baofei; Lei, Shan; Xie, Peng; Yu, Wenfeng (Frontiers in Neurology, 2025)
IntroductionDue to the anti-inflammatory and antioxidant properties of cynaroside (Cyn), it may be useful in the treatment of cerebral ischemia/reperfusion injury (I/R). This study aims to evaluate the effect of Cyn on cerebral ischemia/reperfusion injury.MethodsTransient middle cerebral artery occlusion model (tMCAO) and oxygen and glucose deprivation/reperfusion (OGD/R) microglia models were used to evaluate the effect of Cyn. The direct interaction between Cyn and Alox15 was investigated through bioinformatics, molecular docking and biolayer interferometry.ResultstMCAO mice treated with Cyn show improved neurological deficits, reduced infarct volume and edema, and inhibition of microglial activation. In addition, Cyn inhibited tMCAO-induced Alox15 expression. Cyn significantly reduced the overproduction of the M1 microglia-regulated pro-inflammatory cytokines NLRP3, ASC, and cleaved caspase-1, as well as the overproduction of IL-1β and IL-18, induced by tMCAO or OGD/R. Cyn also inhibits the expression of Tfrc, COX2, and Acsl4 in tMCAO and OGD/R-treated mice and BV-2 cells.DiscussionThese results suggest that Cyn may attenuate cerebral ischemia/reperfusion injury by inhibiting Alox15 to reduce inflammation and reduce ferroptosis. This study reveals the underlying molecular mechanism of Cyn in the treatment of ischemic stroke.